Stability of organic matter in soils of the Belgian Loess Belt upon erosion and deposition. (31st January 2013) - Wang, X.; Cammeraat, L. H.; Wang, Z.; Zhou, J.; Govers, G.; Kalbitz, K.
Summary Soil erosion has significant impacts on terrestrial carbon (C) dynamics. It removes C‐rich topsoil and deposits it in lower areas, which might result in its stabilization against microbial decay. Subsequently, C‐poor deeper horizons will be exposed, which also affects C stabilization. We analysed factors governing soil organic C (SOC) mineralization in topsoil (5–10 cm) and subsoil (75–100 and 160–200 cm) horizons from two contrasting sites (up‐slope compared with down‐slope) in the Belgian Loess Belt; we refer to these as eroding and depositional sites, respectively. Deposition of eroded soil material resulted in significantly increased SOC contents throughout the entire soil profile (2 m) and microbial biomass C in the topsoil. In a 28‐day incubation experiment we studied effects of O2 concentrations (0, 5 and 20%) and substrate (glucose) availability on C mineralization, soil microbial biomass and CaCl2‐extractable C. Carbon enrichment at the depositional site was accompanied by weak mineralization rates and small contents of water‐extractable organic C. Addition of glucose stimulated microbial growth and enhanced respiration, particularly in the subsoil of the depositional site. Availability of O2 showed the expected positive relationship with C mineralization in topsoils only. However, small O2 concentrations did not decrease C mineralization in subsoils, indicating that controls on C dynamics were different in top‐ and subsoils. We conclude that reduced C mineralization contributed to C accumulation as observed at depositional sites, probably because of poor availability of C in subsoil horizons. Limited availability of O2 in subsoils can be excluded as an important control of soil C accumulation. We hypothesize that the composition of the microbial community after burial of the organic‐rich material might play a decisive role.